2015
DOI: 10.1155/2015/870520
|View full text |Cite
|
Sign up to set email alerts
|

Induced Resistance in Solanum lycopersicum by Algal Elicitor Extracted from Sargassum fusiforme

Abstract: Tomato (Solanum lycopersicum) production relies heavily on the use of chemical pesticides, which is undesired by health- and environment-concerned consumers. Environment-friendly methods of controlling tomato diseases include agroecological practices, organic fungicides, and biological control. Plants' resistance against pathogens is induced by applying agents called elicitors to the plants and would lead to disease prevention or reduced severity. We investigated the ability of a novel elicitor extracted from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 32 publications
(39 reference statements)
1
9
0
Order By: Relevance
“…vesicatoria , early blight ( Alternaria linariae ), late blight ( Phytophthora infestans ), and powdery mildew ( Golovinomyces lycopersici ) are considered the most disastrous problems of tomato [ 43 , 44 ]. For instance, several reports have shown that the application of crude or purified algal preparations protect against a large range of pathogens in tomato seedlings [ 42 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…vesicatoria , early blight ( Alternaria linariae ), late blight ( Phytophthora infestans ), and powdery mildew ( Golovinomyces lycopersici ) are considered the most disastrous problems of tomato [ 43 , 44 ]. For instance, several reports have shown that the application of crude or purified algal preparations protect against a large range of pathogens in tomato seedlings [ 42 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…At least 10 individual plants were used for measuring flowering time in the T 3 or T generations. To determine the significant difference in flowering time of transgenic plants compared with that of Arabidopsis double or triple mutants, the data was analyzed using SPSS software version 12.0 (Sbaihat et al 2015).…”
Section: Generation Of Transgenic Plants and Measurement Of Floweringmentioning
confidence: 99%
“…An important advantage of using the Sargassum biomass is that it contains many active compounds [17,18]. In previous studies, the sulfated fucan oligosaccharide of the other brown seaweed was found to induce several defense responses in many plant species [19,20].…”
Section: Introductionmentioning
confidence: 99%